Konsep Makrifat menurut Ibnu Athaillah al-Sakandari - Moh. Isom Mudin (Universitas Darussalam Gontor, 2016)
This paper discusses about the concept of makrifat and its relevance to the spiritual in modern era. Sufi’s makrifat is not the result of speculative reasoning, but the result of direct testimony. Therefore, the problem to be answered about the essence and experience of divinity has always been a mystery. By analyzing critically, this study resulted in the finding that the concept of makrifat according to Ibnu Ata Allah is the essence of tauhid that combines Islam, Iman and Ihsan. He has explored the aspects of ‘jadzab’ in reaching makrifat. The spiritual experiences toward the essence of divinity which is not represented in the form of witnessing the absolute oneness (syuhūd al-aḥadiyyah) became the main characteristic of his makrifat. This condition is contrary to the ideology of modern materialism that nullify the spiritual and assume that the physical world is the essence of everythings. Thus, according to Ibnu Ata Allah, makrifat has found a great momentum wherein it reach this level, ‘ārif must look at the world on Allah’s will. Besides that, an ārif will see at the absolute oneness (syuhūd al-aḥadiyah) which is outside the scope of human reasoning when they get the level of wusṣūl in makrifat form. The view that be felt by ‘ārif bi Allāh give their psychological side affects. They felt fanā, jam`, ghaibah, sakr and another more perfect condition. The testimony and their spiritual condition affecting their vision on the world. Where they watched fi`l by fi`l, ṣifah by sifah also dzāt by dzāt .